2009
DOI: 10.1136/jnnp.2008.155671
|View full text |Cite
|
Sign up to set email alerts
|

High CSF transforming growth factor   levels after subarachnoid haemorrhage: association with chronic communicating hydrocephalus

Abstract: Acutely measured levels of TGFbeta1/beta2 in the CSF of patients with subarachnoid haemorrhage are thus potential prognostic biomarkers for the subsequent development of chronic communicating hydrocephalus, indicating likely dependency on CSF shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 40 publications
3
39
2
Order By: Relevance
“…Interestingly, elevated levels of TGF-β 1 in the CSF of patients with SAH have already been reported in the literature [16,17,18], and are in line with our observations in the peripheral blood. Moreover, high CSF concentrations of TGF-β 1 were significantly associated with the development of chronic communicating hydrocephalus [16,17,18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, elevated levels of TGF-β 1 in the CSF of patients with SAH have already been reported in the literature [16,17,18], and are in line with our observations in the peripheral blood. Moreover, high CSF concentrations of TGF-β 1 were significantly associated with the development of chronic communicating hydrocephalus [16,17,18].…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, high CSF concentrations of TGF-β 1 were significantly associated with the development of chronic communicating hydrocephalus [16,17,18]. In our study, no association was found for development of hydrocephalus and TGF-β 1 values.…”
Section: Discussioncontrasting
confidence: 51%
“…In our experiment, TGF-b1 was not observed in the CSF in any of the four patient groups. Our results differ from previous serial analyses of TGF-b1 in patients after SAH [17,30]. These differences may be related to sampling time after SAH.…”
Section: Cytokines and Growth Factorscontrasting
confidence: 85%
“…BMP7 [24], TGFb1 and 2 [25][26][27][28][29], PDGF-BB [30], NGF [31] FGF-2 [32,33] and TGF-a [34] have all been identified. Only in a few circumstances are their effects on leptomeningeal cells known.…”
Section: Discussionmentioning
confidence: 99%